Peningkatan Hasil Belajar Pembelajaran Daring Melalui Model Project Based Learning Berbantu Platform Zoom Meeting - Yulaikah Iswandari (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Abstract Researchers are interested in revealing efforts to improve student learning outcomes through the Project Based Learning model for grade V students in science subjects Food Chains and Food Nets at SD Islam Al Umar Ngargosoka, Srumbung. The research method used was Classroom Action Research (PTK) using a research model developed by Kemmis and Mc Taggart. This study consisted of three cycles. The average value obtained in the posttest cycle I was 7, in cycle II was 82 and in cycle III 94 The percentage of student learning completeness also increased, cycle I reached 76%, cycle II reached 88% and cycle III 94%. The results of these studies indicate that the use of the Project Based Learning model can improve student learning outcomes in science subjects. So it is hoped that the Project Based Learning model can be used as one of the science learning models in elementary schools that further develops the abilities of students.